Low dose of GRP78-targeting subtilase cytotoxin improves the efficacy of photodynamic therapy in vivo - GABRYSIAK, MAGDALENA (Oncol Rep, 2016)
Photodynamic therapy (PDT) exerts direct cytotoxic effects on tumor cells, destroys tumor blood and lymphatic vessels and induces local inflammation. Although PDT triggers the release of immunogenic antigens from tumor cells, the degree of immune stimulation is regimen-dependent. The highest immunogenicity is achieved at sub-lethal doses, which at the same time trigger cytoprotective responses, that include increased expression of glucose-regulated protein 78 (GRP78). To mitigate the cytoprotective effects of GRP78 and preserve the immunoregulatory activity of PDT, we investigated the in vivo efficacy of PDT in combination with EGF-SubA cytotoxin that was shown to potentiate in vitro PDT cytotoxicity by inactivating GRP78. Treatment of immunocompetent BALB/c mice with EGF-SubA improved the efficacy of PDT but only when mice were treated with a dose of EGF-SubA that exerted less pronounced effects on the number of T and B lymphocytes as well as dendritic cells in mouse spleens. The observed antitumor effects were critically dependent on CD8(+) T cells and were completely abrogated in immunodeficient SCID mice. All these results suggest that GRP78 targeting improves in vivo PDT efficacy provided intact T-cell immune system.